2018
DOI: 10.1016/j.gore.2018.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Nivolumab use for BRCA gene mutation carriers with recurrent epithelial ovarian cancer: A case series

Abstract: Tumors deficient in DNA mismatch repair are known to display increased susceptibility to immune checkpoint inhibitors due to accumulation of DNA damage and increased neoantigen load. This suggests that deficiency in the BRCA-related DNA repair mechanism may also be a surrogate marker for immunotherapy response. The aim of this study was to examine the efficacy of the immune checkpoint inhibitor, nivolumab, in women with BRCA gene mutations and recurrent müllerian cancer. This retrospective case series followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 11 publications
1
16
1
Order By: Relevance
“…51 Cases with BRCA mutations showed overall increased mutational burden harboring higher response rates to immunotherapies, including immune checkpoint blockade. 52 However, comparison of the expression patterns of PD-L1 and PDK1 in cases with mutant and wild-type BRCA in this study revealed no influence of BRCA mutation on PD-L1 or PDK1 levels in ovarian cancer.…”
Section: Discussioncontrasting
confidence: 58%
“…51 Cases with BRCA mutations showed overall increased mutational burden harboring higher response rates to immunotherapies, including immune checkpoint blockade. 52 However, comparison of the expression patterns of PD-L1 and PDK1 in cases with mutant and wild-type BRCA in this study revealed no influence of BRCA mutation on PD-L1 or PDK1 levels in ovarian cancer.…”
Section: Discussioncontrasting
confidence: 58%
“…BRCA and homologous recombination deficiency (HRD) status were also evaluated in the KEYNOTE-100 study, but no differences were observed between responders and non-responders [35]. However, in a small series of mutated BRCA patients with recurrent EOC, the use of salvage therapy with nivolumab resulted in an ORR of 67% (4 of 6 patients) [51].…”
Section: Brca Statusmentioning
confidence: 99%
“… 3 Non-MMR DNA repair pathways may increase somatic mutation rates, but their association with ICI response has not been examined systematically. 10 …”
Section: Introductionmentioning
confidence: 99%